Clinico-radiologic Spectrum and Outcome of Pediatric Acquired Demyelinating Disorders of Central Nervous System: A Retrospective Indian Tertiary Care Hospital Cohort - Prithviraj, Ramakrishna; Banerjee, Bidisha; Acharya, Ullas V.; Hafis, Muhammed; Sashidharan, Sruthi (Neuropediatrics, 2024)
Background Pediatric acquired demyelinating syndrome (ADS) constitutes a group of treatable disorders with acute neurologic dysfunction. Neuroimaging has played a significant role in diagnosis of ADS. We describe clinico-radiologic spectrum, outcomes, and comparison of the groups: acute disseminated encephalomyelitis (ADEM), neuromyelitis optica spectrum disorder (NMOSD), clinically isolated syndrome (CIS), multiple sclerosis (MS), and myelin oligodendrocyte glycoprotein antibody-associated disorders (MOGAD).Methods Retrospective review of 70 children with ADS at a tertiary care hospital over 15 years (2008–2023) was performed. Diagnosis was assigned as per International Pediatric Multiple Sclerosis Study Group criteria 2016. Fisher's exact and chi-square tests were applied.Results Thirty-nine boys and 31 girls aged 8.2 ± 4.0 years with CIS (n = 27), ADEM (n = 16), NMOSD (n = 13), MS (n = 1), and MOGAD (n = 13) were included. Clinical syndromes with positive significant association included polyfocal symptoms, encephalopathy in ADEM, optic neuritis (ON) in MOGAD, brainstem, area postrema syndrome in NMOSD. MOGAD presented with atypical presentations like prolonged fever (PF; 76.9%) and aseptic meningitis (23%). Seropositivity for myelin oligodendrocyte glycoprotein immunoglobulin-G was 62% and for NMO-IgG 2.6%. Neuroimaging of MOGAD showed lesions predominantly in basal ganglia/thalami (69.2%), optic nerve (46.2%), and cerebellum (46.2%). Imaging patterns between ADEM and MOGAD were comparable except for more ON (p = 0.004), spinal cord (p = 0.01), and cerebellar lesions (p = 0.03) in MOGAD. Area postrema lesion was unique to NMOSD. All patients received immunotherapy, of whom 91.4% (n = 64) had good recovery, 8.6% (n = 6) had functional limitation on modified Rankin scale at discharge, and 12 (17.1%) relapsed.Conclusion The largest group was CIS. Seropositivity of MOG was high with atypical presentations like PF and aseptic meningitis. Specific neuroimaging patterns correlated with ADS categories. Short-term outcome with immunotherapy was favorable in spite of relapses.
Keywords: acute disseminated encephalomyelitis; neuromyelitis optical spectrum disorder; clinically isolated syndrome; MOG antibody disease; basal ganglia/thalami